Enhanced Photoresponsivity of Multilayer MoS 2 Phototransistor Using Localized Au Schottky Junction Formed by Spherical-Lens Photolithography - Lee, Sanghyun; Park, Jinwoo; Yun, Yeojun; Lee, Jaejin; Heo, Junseok (Advanced Materials Interfaces, 2019)
The photoresponsivity of a MoS 2 phototransistor is limited owing to its low light absorption. Many studies aiming to improve the photoresponsivity have enhanced the light absorption in MoS 2 by optical resonance or by integrating an absorbing layer. However, the light-absorbing overlayer changes the spectral photoresponsivity and forms a leakage path. In this study, an enhanced photoresponsivity of a multilayer MoS 2 phototransistor is obtained by localized Au/MoS 2 Schottky junctions without light-absorbing overlayer. Au disks are formed on the MoS 2 surface using a simple spherical-lens photolithography technique, forming localized Schottky junctions between MoS 2 and Au disks. Photogenerated holes drift to the interface due to the built-in electric field around the Schottky junction and are trapped in the interface states between MoS 2 and Au disks. The holes captured in the states lead to photogain. Consequently, after the patterning of the Au disks, the photoresponsivity is enhanced 8.2 times while maintaining other electrical properties. The findings obtained in this study are very valuable as the photoresponsivity enhancement is achieved using the simple method with a minimal damage to MoS 2 . The multilayer MoS 2 phototransistor with Au disks is promising for applications in next-generation optoelectronics with photodetector devices.
Keywords: Built-in electric fields; Enhanced photoresponsivity; MoS2; Optical resonance; photogain; Photogenerated holes; Photoresponsivity; Schottky junctions; MoS 2; photogain; photoresponsivity; phototransistor; Schottky junction